How Doctors Report: A Corpus-based Contrastive Analysis of Reporting Verbs in Research Article Introductions Published in International and Thai Medical Journals - Jirapanakorn, Naruemol (The Bangkok Medical Journal, 2012)
OBJECTIVES: This study aims to explore the differences in the use of reporting verbs between medical research article introductions published in the international and Thai medical journals, using a corpus-based approach. MATERIALS AND METHODS: Two comparable corpora were compiled from 50 medical research article introductions published in English language during 2005-2009: 25 introductions from 5 international journals and 25 introductions from 5 Thai journals. All reporting verbs were identified and categorized into 3 types: experimental, discourse and cognition verbs. The differences in the list of these reporting verbs and their usage were examined. RESULTS: The frequency of occurrence of reporting verbs in the international corpus was 12.61 per 1,000 words, while that of the Thai corpus was 9.87 per 1,000 words. The international journals used 40 reporting verbs, whereas 24 reporting verbs were identified in the Thai journals. In all three categories, the international journals used more reporting verbs than the Thai medical journals. CONCLUSION: Reporting verbs were used in the international medical research articles with higher frequencies and a wider variety than the Thai medical research articles. The list and examples from both corpora would assist medical researchers in using reporting verbs to write their research articles appropriately.